2021
DOI: 10.1039/d1nj01333e
|View full text |Cite
|
Sign up to set email alerts
|

Fight against COVID-19 pandemic with the help of carbon-based nanomaterials

Abstract: COVID-19, this viral respiratory disease, which was first reported in Wuhan, China, in 2019 and subsequently, spread around the world, is caused via the coronavirus SARS-CoV-2. These days, all countries...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 54 publications
0
33
0
Order By: Relevance
“…This aptitude makes the mask able to elevate its surface temperature above 70ºC within 5 minutes when exposed to sunlight, a temperature which is adequate for SARS-CoV-2 inhibition [124]. The antiviral activity of carbon-based materials has also been attributed to a photothermal antiviral mechanism and/or reactive oxygen species generation [143]. A method for functionalizing commercially available surgical masks by a dual-mode laser-induced forward transfer method to deposit few-layer graphene onto nonwoven fabrics with superhydrophobicity, and outstanding self-cleaning and photothermal properties has been reported [105] (Figure 10).…”
Section: Carbon-derived and Photoactive Materialsmentioning
confidence: 99%
“…This aptitude makes the mask able to elevate its surface temperature above 70ºC within 5 minutes when exposed to sunlight, a temperature which is adequate for SARS-CoV-2 inhibition [124]. The antiviral activity of carbon-based materials has also been attributed to a photothermal antiviral mechanism and/or reactive oxygen species generation [143]. A method for functionalizing commercially available surgical masks by a dual-mode laser-induced forward transfer method to deposit few-layer graphene onto nonwoven fabrics with superhydrophobicity, and outstanding self-cleaning and photothermal properties has been reported [105] (Figure 10).…”
Section: Carbon-derived and Photoactive Materialsmentioning
confidence: 99%
“…Carbon-based nanomaterials such as graphene oxide and carbon nanotubes (CNTs) with great features like unique construction, outstanding mechanical/chemical stability, and antimicrobial performance [ 50 , 51 ] have been employed broadly in fabrication air filters which Table 2 shows many of them. The following are some of their applications in this regard.…”
Section: The Role Of Carbon-based Nanomaterials For Fabrication Of Ef...mentioning
confidence: 99%
“…Studies showed that graphene materials interact with viruses via binding and wrapping mechanisms. These materials act as virustatic inhibitors, resulting in the inhibition of virus interaction with host cells (Mallakpour et al, 2021). A series of graphene derivatives altering the length of aliphatic chains were synthesized to investigate the inhibitory activity against SARS-CoV-2 (Donskyi et al, 2021).…”
Section: Carbon Nanomaterialsmentioning
confidence: 99%